CHALLENGES AND PROSPECTS: POLICY FORMULATION OF THE DEATH PENALTY FOR LAW ENFORCEMENT AGAINST CORRUPTORS IN INDONESIA - Ashidiq, Abdul Rahman; Arifah, Arifah; Wismadi, Muhammad Tsaqif; Lestari, Amanda Putri Febi (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2024)
The policy of formulating the death penalty for perpetrators of criminal acts of corruption in Indonesia has given rise to complex debate in society. This research explores the policy of formulating the death penalty for perpetrators of criminal acts of corruption in Indonesia with a focus on analyzing its effectiveness, impact on human rights, and moral and ethical implications. The research method used is a normative juridical approach using the analysis of law enforcement system theory and criminal theory. Data was collected through literature studies covering laws, regulations and related legal literature. The research results show that the policy of formulating the death penalty creates a complex debate in society. Law enforcement system theory provides insight into the integration of these policies with the law enforcement system, while punishment theory opens up ethical and philosophical insights. There are significant differences of opinion among the public regarding the effectiveness, morality and impact on human rights of this policy. Keywords: Death Penalty Policy, Corruption Crimes, Law Enforcement System, Sentencing Theory